THE SYSTEM OF FORMING THE CONTROL MODE OF THE ELECTRIC DRIVE DURING THE START-UP OF THE VIBRATION MACHINE (World Science, 2021)
The above resonance vibration machines are widely used in various industries, but have a number of shortcomings associated with increasing of the oscillations amplitude when passing the resonance zone during start-up. It is noted that to reduce the oscillations amplitude and quickly pass the resonance zone, it is advisable to use a frequency-controlled electric drive with the formation of additional control effects. Features of frequency start of the electric drive of the vibration machines are noted. The structure of the electric drive control system during passing the resonance zone in the process of starting the above resonance vibration machine in the form of a block-scheme is proposed. The algorithm of operation of the control system is given.